Diretrizes urbanísticas e construtivas para cidades de clima semi-áridos: estudo de caso na cidade de Monteiro - Lima, Mariana Brito de (2007)
In order to adequate town planning and architecture to the climate in a certain place it is necessary to build spaces that offer comfortable conditions for human beings. As the hot and dry climate presents more challenges regarding higrotermic comfort in the environment, it implies a major need to create micro-climates and, thus, town planning and construction solutions that ease the climatic conditions and attend human needs of environmental comfort. To be able to understand the environmental problems that result from the town planning in a certain region it is essential to study the urban climate in that region. The definition of the study object in this dissertation is, in this context, the interaction between town planning phenomena and the climate in the towns, specifically the town of Monteiro, localized in the semi-arid region in the interior of the State of Paraíba in North-Eastern Brazil. The issue put as the problem is how to elaborate urban and architectonic plans for towns with semi-arid climate, that respond to the human needs of environmental comfort. With the purpose to answer this question, a field study was realized with five portable climatologic stations distributed in different points in the town. These climatologic stations measured the velocity and the direction of the wind, the temperature and the relative humidity of the air during November, historically considered the hottest month of the year. The climatic data and the environmental variables of the town, such as soil use, density, forestation, orientation of the streets, etc, were studied using the methodology proposed by Monteiro (1976) and Bustos Romero (2001). The first part of this work presents the climatic data from every measuring point, comparing its external and internal behaviour, with the purpose to understand how different kinds of buildings, and the space around them, contribute to smoothen the climatic conditions within every building. The second part analyses and compares the data from all the points with the climatic data from the closest meteorological station, localized in the neighbouring municipality of Sertânia, State of Pernambuco. After having analyzed the configurations of the urban climate in question and having correlated the possible problems that can have influenced the climate in every measuring point, the study indicates guidelines for town planning and constructions that can improve the environmental comfort in the town of Monteiro.